2022
DOI: 10.1002/agj2.21019
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon stock is improved by cover crops in a tropical sandy soil

Abstract: Soil organic matter plays an important role in soil quality. In sandy soils of tropical regions, high biological activity in the soil accelerates mineralization and limits increases in organic matter content. The objective of this study was to evaluate the total organic C stock and the chemical and physical fractions of organic C in a sandy soil in Presidente Bernardes, São Paulo, Brazil, as a function of cover cropping with different combinations of grasses and legumes between 2015 and 2020. The treatments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…contents varied in all cereal-legume intercropping combinations. The results concur with Cordeiro et al [21], who reported increased soil particulate organic content due to intercropping. The Results of this study included the following, from the largest to the lowest: millet and beans (8.92%), millet and soya (8.85%), millet and groundnuts (6.57%), millet sole (7.66%), local orange maize and soya (6.20%), sorghum and groundnuts (6.05%), sorghum sole (5.74%), local orange maize sole (5.54%), sorghum and beans (5.22%), local orange maize and beans (4.65%), sorghum and soya (4.36%), and local orange maize and groundnuts (4.23%) (Fig.…”
Section: Soil Particulate Organic Matter (%) Under the Maizelegume In...supporting
confidence: 92%
“…contents varied in all cereal-legume intercropping combinations. The results concur with Cordeiro et al [21], who reported increased soil particulate organic content due to intercropping. The Results of this study included the following, from the largest to the lowest: millet and beans (8.92%), millet and soya (8.85%), millet and groundnuts (6.57%), millet sole (7.66%), local orange maize and soya (6.20%), sorghum and groundnuts (6.05%), sorghum sole (5.74%), local orange maize sole (5.54%), sorghum and beans (5.22%), local orange maize and beans (4.65%), sorghum and soya (4.36%), and local orange maize and groundnuts (4.23%) (Fig.…”
Section: Soil Particulate Organic Matter (%) Under the Maizelegume In...supporting
confidence: 92%
“…In addition, biomass was not significantly correlated with SOM (Figure 2), which could be partially due to high spatial heterogeneity of soil properties masking trends among different treatments (Figure 4). These results further highlight that keeping soil covered continuously could be more important than selecting certain species or mixtures in terms of building SOM and soil health (Calegari et al, 2008;dos Santos Cordeiro et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…The MBC is one of the most labile of the carbon pools comprising organic matter, which varies with different management practices (Zhang et al, 2021 ; Cordeiro et al, 2022 ). Nutrient availability potential represents an increase in MBC than an increase in total organic matter (Sharma et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%